Overpaint removal from easel paintings using an LQS Nd:YAG laser: The first validation study. (August 2015) - Siano, Salvatore; Osticioli, Iacopo; Pavia, Alessandro; Ciofini, Daniele
<x content-type="archive" xml:space="preserve">Abstract</x> In this work, laser ablation has been applied for removing overpaint found on the reverse of a signed easel painting by Giacomo Balla, one of the founding members of the Futurist movement. After unsuccessful attempts to remove the overpaint layers selectively using organic solvents, a long Q-switched Nd:YAG laser (1064 nm, 120 ns) ablation was successfully trialled, enabling the planning of complete uncovering of a hidden artwork by laser treatment. Laser cleaning was accompanied with a thorough characterisation of the original pigments, binders, and overpaint using Raman and FTIR spectroscopy, along with stratigraphic examination combined with optical and ESEM-EDX analysis. In parallel systematic experimentation on samples simulating the layers to be removed was carried out to interpret the laser removal processes being exploited and fine-tune the treatment.